2019
DOI: 10.1107/s2052520619013350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the order–disorder phase transitions of B cations in AB1/2 B′′1/2O3 perovskites

Abstract: Perovskite‐like oxides AB′1/2B′′1/2O3 may experience different degrees of ordering of the B cations that can be varied by suitable synthesis conditions or post‐synthesis treatment. In this work the earlier proposed statistical model of order–disorder phase transitions of B cations is extended to account for the effect of pressure. Depending on the composition, pressure is found to either increase or decrease the order–disorder phase transition temperature. The change in transition temperature due to pressure i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As a result, the pressure has a major impact on the optical and electrical properties, which reveals promising qualities for photovoltaic (PV) and optoelectronic applications. Hydrostatic pressure has shown remarkable success in improving the physical characteristics of halide perovskites. Usually, hydrostatic pressure modifies the lattice parameters, displacement of cations and anions, , rotation of octahedral cages, phase transitions, , etc. As pressure is applied to metal halides, the volume of the unit cell and the lattice constants both drop. , Recent studies have demonstrated that hydrostatic pressure can decrease the band gap in inorganic halide perovskites such as KCaCl 3 , RbYbF 3 , and CsGeI 3 , leading to an increase in conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the pressure has a major impact on the optical and electrical properties, which reveals promising qualities for photovoltaic (PV) and optoelectronic applications. Hydrostatic pressure has shown remarkable success in improving the physical characteristics of halide perovskites. Usually, hydrostatic pressure modifies the lattice parameters, displacement of cations and anions, , rotation of octahedral cages, phase transitions, , etc. As pressure is applied to metal halides, the volume of the unit cell and the lattice constants both drop. , Recent studies have demonstrated that hydrostatic pressure can decrease the band gap in inorganic halide perovskites such as KCaCl 3 , RbYbF 3 , and CsGeI 3 , leading to an increase in conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrostatic pressure has shown remarkable success in improving the physical characteristics of halide perovskites. 27 30 Usually, hydrostatic pressure modifies the lattice parameters, 31 displacement of cations and anions, 32 , 33 rotation of octahedral cages, 34 phase transitions, 35 , 36 etc. As pressure is applied to metal halides, the volume of the unit cell and the lattice constants both drop.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of enhancing physical properties of halide perovskites, the application of hydrostatic pressure has demonstrated tremendous results 27 32 . Usually, hydrostatic pressure modifies the lattice parameters 33 , displacement of cation and anion 34 , 35 , rotation of octahedral cages 36 , phase transitions 37 , 38 , etc. In the case of metal halides, structural properties, like lattice constants and unit cell volume decrease with increasing pressure 29 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Since pressure plays a crucial role in the determination of material properties, it is vital to investigate the selected systems under pressure in order to finetune the properties of halide perovskites, which have shown tremendous results in recent years [40][41][42][43][44][45]. The pressure applied to perovskites can alter their properties in a range of ways, including the lattice parameter [46], the displacement of cations and anions [47,48], the rotation of octahedral cages [49], phase transitions [50,51], etc For metal halides, pressure normally modifies the physical and chemical properties, such as shrinkage of lattice volume, reduction of the band gap with decreasing the lattice parameter, and enhanced optoelectronic performance [37-39, 42, 44, 45]. In recent works, CsSnCl 3 , RbSnX 3 (X = Cl, Br), AGeI 3 (A = Rb, K), AGeF 3 (A = K, Rb), and RbGeX 3 (X = Cl, Br) exhibit noticeable increments in optical absorption in the visible range under elevated pressure [17,[52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%